TINGKAT PENGETAHUAN IDENTIFIKASI INFORMASI BOHONG ATAU HOAKS DALAM GRUP WHATSAPP DI MASYARAKAT DENPASAR - Pebriyanti, Komang Gina; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 1 (2020): Jurnal Ilmu Komunikasi 2020, 2020)
ABSTRACT The growth of information technology makes hoax or false information spread very easily. There are 733 hoax complaints and 43 hoax contents  were spread in Whatsapp media from 2018 to 2019. Whatsapp is the second-place platform for hoax spreaders (56,55%) after Facebook (82,25%). This study aims to measure the level of knowledge of Denpasar community identification of hoax in Whatsapp group. This study uses descriptive quantitative research methods with the concept of knowledge divided into 6 levels, Know, Comprehension, Application, Analysis, Synthesis, and Evaluation. The sampling technique was purposive sampling. Data obtained by distributing questionnaires with 230 respondents in March 2020 that were measured using  Likert scale. The results show that the Denpasar community have very high level of identification knowledge in identifying hoax or false information in Whatsapp group but it is known that men with background senior high school have a better level of identification knowledge than women. Keyword: Denpasar, Hoax, Knowledge, Whatsapp Group